Invasive Assessment of Coronary Physiology Predicts Late Mortality After Heart Transplantation. Issue 20 (17th May 2016) - Yang, Hyoung-Mo; Khush, Kiran; Luikart, Helen; Okada, Kozo; Lim, Hong-Seok; Kobayashi, Yuhei; Honda, Yasuhiro; Yeung, Alan C.; Valantine, Hannah; Fearon, William F.
Abstract : Background—: The aim of this study is to determine the prognostic value of invasively assessing coronary physiology early after heart transplantation. Methods and Results—: Seventy-four cardiac transplant recipients had fractional flow reserve, coronary flow reserve, index of microcirculatory resistance (IMR), and intravascular ultrasound performed down the left anterior descending coronary artery soon after (baseline) and 1 year after heart transplantation. The primary end point was the cumulative survival free of death or retransplantation at a mean follow-up of 4.5±3.5 years. The cumulative event-free survival was significantly lower in patients with a fractional flow reserve <0.90 at baseline (42% versus 79%; P =0.01) or an IMR ≥20 measured 1 year after heart transplantation (39% versus 69%; P =0.03). Patients in whom IMR decreased or did not change from baseline to 1 year had higher event-free survival compared with patients with an increase in IMR (66% versus 36%; P =0.03). Fractional flow reserve <0.90 at baseline (hazard ratio, 0.13; 95% confidence interval, 0.02–0.81; P =0.03), IMR ≥20 at 1 year (hazard ratio, 3.93; 95% confidence interval, 1.08–14.27; P =0.04), and rejection during the first year (hazard ratio, 6.00; 95% confidence interval, 1.56–23.09; P =0.009) were independent predictors of death/retransplantation, whereas intravascular ultrasound parameters were not. Conclusions—: Invasive measures of coronary physiology (fractional flow reserve and IMR) determined early after heart transplantation are significant predictors of late death or retransplantation.